EFEKTIFITAS METODE CERAMAH DALAM PENYAMPAIAN DAKWAH ISLAM: Studi pada Kelompok Pengajian di Perumahan Mojosongo Permai Kabupaten Boyolali - Maryatin, Maryatin (Jurnal Ilmu Dakwah, 2014)
This is a qualitative research that generates two discriptive forms namely people’s written or spoken and also  the behavior that can be observed. Through the qualitative approach which emphasised on the usage of observational techniques involved (participant observation) and in-depth interviews (indepth-interview) in date collection. Participant observation techniques used to obtain a detailed picture of the society condition in the residential neighbourhood of Mojosongo Permai. The results of this research showed that the implementation of payroll in the Mojosongo Permai residential neighborhood that generally has two substantial investigations, investigations of women called "study of the women’s majlis ta'lim in Mojosongo Permai" and Men’s yasinan. Men’s Yasinan held once in a month is not specified because it depends on the encountering citizens. Participants of the study that consists of women in a Moslem Residential area of  Mojosongo Permai. Time discussion executed in the afternoon after the ASR prayer. *** Penelitian ini merupakan penelitian kualitatif yang menghasilkan dua bentuk deskripsi yaitu tulisan orang atau lisan dan juga perilaku yang dapat diamati. Pendekatan kualitatif yang menekankan pada penggunaan teknik pengamatan terlibat (observasi partisipan) dan wawancara mendalam (indepth interview-) dalam mengumpulkan data. Teknik observasi partisipan digunakan untuk memperoleh gambaran rinci tentang kondisi masyarakat di lingkungan pemukiman Mojosongo Permai. Hasil penelitian ini menunjukkan bahwa pelaksanaan penggajian di lingkungan perumahan Mojosongo Permai terdapat dua kegiatan yaitu majlis taklim perempuan dan yasinan pria. Yasinan Pria diadakan sekali dalam satu bulan tidak ditentukan karena tergantung pada warga hadapi. Objek  studi yaitu muslimat di daerah Perumahan Mojosongo Permai yang diselenggarakan setiap sore setelah sholat ashar